2017
DOI: 10.3390/nu9101114
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Nutritional Support of Adult Patients in the Setting of Cirrhosis

Abstract: Aim: The aim of this work is to develop a pragmatic approach in the assessment and management strategies of patients with cirrhosis in order to optimize the outcomes in this patient population. Method: A systematic review of literature was conducted through 8 July 2017 on the PubMed Database looking for key terms, such as malnutrition, nutrition, assessment, treatment, and cirrhosis. Articles and studies looking at associations between nutrition and cirrhosis were reviewed. Results: An assessment of malnutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Evaluating the dietary intake helps physicians and dieticians understand poor food habits, dietary choice, and excessive consumption. Suitable management of malnutrition involves establishing daily a diet that includes a restricted calorie intake and diverse nutrient consumption ( 45 ). Using the FFQ, the quantity of daily intakes was calculated based on the portion size and consumption frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the dietary intake helps physicians and dieticians understand poor food habits, dietary choice, and excessive consumption. Suitable management of malnutrition involves establishing daily a diet that includes a restricted calorie intake and diverse nutrient consumption ( 45 ). Using the FFQ, the quantity of daily intakes was calculated based on the portion size and consumption frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Patient preferences and views should be incorporated in the CPGs development process for facilitating CPGs acceptability and compliance by the target group . With the majority of cirrhotic patients demonstrating decreased food intake as a result of digestive problems and hepatic encephalopathy, and many others adhering to restrictive diets and heavy alcohol intake, pragmatic and feasible CPGs are needed for increased adherence . Additionally, patient engagement has already been identified as an indicator of improved care quality in cirrhosis …”
Section: Discussionmentioning
confidence: 99%
“…Watermelon rind contains significant quantity of antioxidant phytochemicals [22]. Alkaloids, flavonoids and phenols possess antioxidant properties [18]. Several studies have revealed the positive correlation between oxidative stress and cellular damage [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Experiment to determine the liver function biomarkers were carried out using the standard laboratory procedures [14]. The biomarkers tested for include; alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total proteins (TP), bilirubin and albumin [18]. This test was carried out on blood samples collected on day 42 of the experimental period.…”
Section: Liver Function Testsmentioning
confidence: 99%